Fostering environmental responsibility with JellyBean: a Google Cardboard VR-based case study on cultivating awareness in middle and high school students about marine ecology and the impact of everyday pollutants - Roy, Tania; Sparra, Hunt Jackson; Skripnikov, Andrey; Gilchrist, Sandra (Frontiers in Virtual Reality, 2025)
This paper presents a Google Cardboard VR simulation to raise awareness among participants aged 11 to 16 about marine ecosystem protection. Focusing on the impact of everyday pollutants on sea turtles, a user study (N = 12) gauged the VR sessions’ impact on student motivation. Mixed-effects modeling was conducted on Likert scale ratings on both the pre- and post-session surveys, finding scores for motivation to learn about nature- and VR-related topics to be significantly higher than 3 (“Neither agree or disagree”) after the VR simulation, while also showing that the simulation had some impact on increasing participant interest across both environmental and VR topics. Qualitative feedback emphasized the desire for more interactivity, improved graphics, and enhanced authenticity. Despite these suggestions, participants effectively grasped the educational message, highlighting VR’s potential in environmental conservation education. This study’s findings underscore the potential of VR-based educational tools in fostering a deeper understanding and commitment among young students towards environmental stewardship, suggesting a promising avenue for integrating technology into environmental education curricula.